Syrphidae (Diptera) from the Greek island of Lesvos, with description of two new species - Ricarte, Antonio; Nedeljković, Zorica; Rotheray, Graham E.; Lyszkowski, Richard M.; Hancock, E. Geoffrey; Watt, Kenneth; Hewitt, Stephen M.; Horsfield, David; Wilkinson, Geoffrey (Zootaxa, 2012)
The results of the hoverfly (Syrphidae) collection by the ‘Malloch Society’ on the Greek island of Lesvos are presented.Fieldwork took place from February to March 2006 and from May to June 2010. An account of 66 species from 28 generais provided including two species new to science, five species new to Greece and data for several rarely recorded species.We describe Eumerus armatus Ricarte and Rotheray sp. nov., a medium size species with red abdomen. We also describeSphiximorpha hiemalis Ricarte, Nedeljković and Hancock sp. nov., a hairy species with distinctive colour and pollinositypatterns and abdomen shape. The female of Eumerus claripennis Coe, 1957 is described and the male genitalia are figured.The majority of species encountered belonged to the typically Mediterranean genera Eumerus (8 spp.), Merodon (16 spp.)and Paragus (6 spp.). Approximately 71% of the recorded species also occur in Turkey. This supports the idea that West Mediterranean and Anatolian faunas overlap in Lesvos.